2004
DOI: 10.1177/0883911504041602
|View full text |Cite
|
Sign up to set email alerts
|

Linear Type Azo-Containing Polyurethanes for Colon-Specific Drug Delivery

Abstract: New biodegradable polyurethanes containing azo-linked polymeric prodrugs of 5-aminosalicylic acid (5-ASA) in the main chain were prepared by reacting 1,6-Hexamethylenediisocyanate (HDI) with 3,30-azobis(6-hydroxy benzoic acid) (ABHB) and 5-[4-(hydroxyl phenyl) azo] salicylic acid (HPAS) as azo derivatives of 5-ASA. The polymers were characterized by FTIR and 1H-NMR spectroscopy. The hydrolysis of polyurethane containing azoderivatives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It is expected that at tumor pH, the doxorubicin-loaded nanoparticles made of Fe 3 O 4 -PLGA-PEG can show enhanced cytotoxicity compared with that at normal pH. [70][71][72][73][74] In this paper, higher and faster doxorubicin release was observed for Fe 3 O 4 -PLGA-PEG 4000 nanoparticles than for Fe 3 O 4 -PLGA-PEG 3000 and Fe 3 O 4 -PLGA-PEG 2000 at 12 hours. This difference could be to the presence of PEG 4000 in the PLGA chains.…”
Section: Discussionmentioning
confidence: 88%
“…It is expected that at tumor pH, the doxorubicin-loaded nanoparticles made of Fe 3 O 4 -PLGA-PEG can show enhanced cytotoxicity compared with that at normal pH. [70][71][72][73][74] In this paper, higher and faster doxorubicin release was observed for Fe 3 O 4 -PLGA-PEG 4000 nanoparticles than for Fe 3 O 4 -PLGA-PEG 3000 and Fe 3 O 4 -PLGA-PEG 2000 at 12 hours. This difference could be to the presence of PEG 4000 in the PLGA chains.…”
Section: Discussionmentioning
confidence: 88%
“…Only a handful of studies have reported the successful use of polyurethanes in drug delivery applications, and their favorable results support further examination of this approach [28][29][30][31][32][33]. Our peptide-based urethane possesses the versatility of commercial polyurethane systems, but lacks the toxicity associated with commercial urethane degradation products.…”
Section: Introductionmentioning
confidence: 71%
“…The colon is known to be a reductive medium in which azo groups can be cleaved with formation of the corresponding amines. The metabolic reduction of azo compounds is considered as an important detoxification route [22,24]. Various prodrugs (sulfasalazine, ipsalazine, balsalazine and olsalazine) have been developed that are aimed to deliver 5-amino salicylic acid (5-ASA) for localized chemotherapy of IBD [25].…”
Section: Resultsmentioning
confidence: 99%